Peran Manajemen Sumber Daya Manusia Dalam Dinas Perumahan Rakyat Dan Kawasan Permukiman Serta Pertanahan (Perkimtan) Kota Padangsidimpuan - Abdelina; Lilis Saryani; Ahmad Sayuti; Makhrani (Yayasan Perguruan Kampus, 2025)
Human Resource Management (HRM) is an important factor in increasing the effectiveness of local government administration. This study aims to analyze the role of MSDM in supporting the operations of the Public Housing and Settlement and Land Areas Office (PERKIMTAN) of Padangsidimpuan Regency. The research uses a descriptive qualitative approach with data collection techniques through interviews, observations, and document studies. The results show that MSDM has a strategic role in the process of recruitment, training, performance evaluation, and career development of employees. However, there are several obstacles such as uneven distribution of human resources, limited training budgets, and a position promotion system that is not fully merit-based. Based on these findings, it is recommended that the agency increase the frequency of technical training, transparency of the career system, and synergy between agencies to improve the quality of public services.